ANTIBACTERIAL AND ANTIFUNGAL STUDIES ON THE BIOSOOT OF COMMON WEEDS (Journal of Pharmaceutical Negative Results, 2022)
Introduction: Biosoot is defined as the smoke or soot generated when burning the biomaterials which may either be of plant or of animal origin. This airborne soot is mostly considered as a negative sign as it may cause different respiratory ailment when they become airborne. However, the impact of this airborne soot depends upon characters like their size and their composition. Due to their chemical or organic compounds associated with the biosoot, their biological activity may differ. Aim: In this study an attempt was made to study the antimicrobial potency of the biosoot of few of the common weeds, Calotropis gigantea, Lantana camara and Parthenium hysterophorus. Methods: The shade dried stem of the plants were burnt to the formation of soot and the soot deposited on the surface of tiles exposed were collected. The methanolic extract of the biosoot were evaluated against the bacteria, Bacillus subtilis, Enterococcus faecalis, Salmonella typhi and Pseudomonas aeruginosa and the fungi, Aspergillus flavus and Aspergillus niger using well diffusion method. Results: The soot of Lantana camara showed high antibacterial activity against Enterococcus faecalis and Bacillus subtilis, Calotropis gigantean against Salmonella typhi and the soot of Parthenium hysterophorus recorded high antibacterial activity against the bacteria, Pseudomonas aeruginosa. Similarly the biosoot of Calotropis gigantea showed better antifungal activity against the fungus, Aspergillus flavus and Parthenium hysterophorus against the fungus, Aspergillus niger. Conclusion: The study aptly demonstrates the utilization of biosoot as an antimicrobial agent when they are in general considered as waste and hazardous. Further, the biosoot of these plants can be potentially utilized in pharmaceutical and cosmeceutical industries after proper evaluation of their toxicity.